2006
DOI: 10.1089/dis.2006.9.236
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Savings Analysis of an Outpatient Management Program for Women with Pregnancy-Related Hypertensive Conditions

Abstract: The aim of this study was to evaluate the cost savings of outpatient management services for women with pregnancy-related hypertensive conditions. The outpatient management program included verbal and written patient education related to the hypertensive disease process during pregnancy as well as self-care procedures. Biometric data (ie, automated blood pressure measurement, qualitative urine protein) were collected at least daily by the patient and transmitted telephonically to a nursing call center. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…An Australian study, comparing urinary protein self-testing by 212 women in clinic, to re-testing by a single nurse, found that self-testing was practical and easily implemented, but did not include an independent reference standard [10]. Several other studies describe providing pregnant women with urine dipsticks to periodically check for protein alongside self-monitoring blood pressure, but have not formally evaluated test performance [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…An Australian study, comparing urinary protein self-testing by 212 women in clinic, to re-testing by a single nurse, found that self-testing was practical and easily implemented, but did not include an independent reference standard [10]. Several other studies describe providing pregnant women with urine dipsticks to periodically check for protein alongside self-monitoring blood pressure, but have not formally evaluated test performance [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…NGT, normal glucose tolerance; FDIU, fetal demise in utero incremental estimates provided by the two studies from the USA and Israel [27,28]. Other studies providing nonincremental and, consequently, higher estimates were disregarded [29,30]. The incremental cost of a stillbirth (including fetal demise in utero), compared with that of a live birth, was assessed to be €2,055, based on a study from the UK providing the most comprehensive costing [31].…”
Section: Methodsmentioning
confidence: 99%
“…In observational studies, home care has been variably defined in terms of activity levels, self-vs. nurse/midwife assessments, and means of communication; [308,309] all involved daily contact and a (usually) weekly outpatient visit [305,308,309].…”
Section: Commentsmentioning
confidence: 99%
“…In observational studies of antepartum home care (vs. inpatient care), hospital admission (25%) [309], re-admission (44%) [305] and maternal satisfaction rates [312] were high, with similar outcomes for either gestational hypertension [313], or mild preeclampsia [305]. Costs were lower with home care [309].…”
Section: Commentsmentioning
confidence: 99%